Análise proteômica diferencial de proteínas superficiais da membrana de Xanthomonas spp. em interação com hospedeiro cítrico - Carnielli, Carolina Moretto (2013)
The citrus canker is an economically important disease for citrus crop. At the moment, there is no effective means of prevention or cure for this disease, which has contributed to citrus canker wide distribution around the world. The etiologic agents are bacteria of the genus Xanthomonas classified into two species, X. citri and X. fuscans. This study aimed to perform the differential proteomic analysis of cell surface proteins of Xanthomonas citri subsp. citri (XAC), the more virulent specie, between infectious (in vivo) and non-infectious (in vitro) conditions of growth. Additionally, the same analysis was performed by shotgun for XAC against the Xanthomonas fuscans subsp. aurantifolii type B (XauB), less virulent specie, both after growth in vivo. Initially, we performed growth curves of both bacteria on leaves of a common citrus host (Citrus aurantifolia) in order to investigate the dynamics of population growth in vivo and the efficiency of cell recovery by two different methods. For proteomic analysis, intact bacterial cells had their surface proteins labeled with fluorescence (DIGE CyDye Fluor minimal dyes), were then lysed and the total protein extract analyzed by differential gel electrophoresis (2D-DIGE), as standardized in this study. Protein profiles were analyzed by DeCyder 7.0 software and spots differentially expressed (ANOVA p <0.05) were isolated from gels, identified by mass spectrometry and search in protein databases of the annotated genome sequence of the bacteria. Seventy-nine spots from XAC were analyzed and thirty different proteins were identified, of which 10 correspond to known membrane or cell surface proteins: Ton-B dependent receptors and OmpA-related proteins exhibited lower expression in infectious condition, differently of Ferric enterobactin receptors, 60 kDa chaperonin (GroEL) and DnaK which showed higher expression after host interaction. XAC and XauB total extraction analysis by shotgun identified just two XAC proteins. Cell surface proteins with increased in vivo expression in virulent strain (XAC) could provide future targets of biotechnological interest for fighting citrus canker for being possibly related to phytopathogenicity and/or host spectrum.